Impact of early versus late tracheotomy on diaphragmatic function assessed by ultrasonography in mechanically ventilated stroke patients - Amr Abdalla Elsayed (Egyptian Journal of Anaesthesia, 2022)
Background Cerebrovascular stroke is one of the most disabling chronic conditions, as it is often associated with devastating long-term neurologic deficits.Design A prospective observational study.Setting Critical Care Units of Alexandria Main University Hospital.Patients 60 adult mechanically ventilated stroke patients of both genders according to sample size calculation.Objective Compare the outcome of early versus late tracheotomy on diaphragmatic function, assessed by ultrasonographic assessment in mechanically ventilated stroke patients.Methods Patients were randomized blindly into two groups: group I was subjected to early bedside percutaneous tracheotomy within 4 days of ICU stay, while group II was tracheostomized after 14 days. A Sonosite Mindray DP10 2015–08 with a 3–5 MHz linear probe was used to assess the diaphragm daily before and after tracheotomy. Measures taken were diaphragmatic excursion (DE) and diaphragmatic thickness (DT). Primary outcome was impact of early tracheotomy on diaphragmatic ultrasound measurements. Secondary outcomes were days of mechanical ventilation, ICU stay, and 28-day mortality.Results After tracheotomy, a significant improvement in DE and DTF in group I was encountered more than group II (p < 0.01). There was a significant decrease in ventilator days, and ICU stay in group I (p < 0.01), without statistical significance in the 28-day mortality (p = 0.612).Conclusion Early tracheotomy in mechanically ventilated stroke patients could improve diaphragmatic ultrasound measurements resulting in rapid weaning off mechanical ventilation and less ICU stay without significant effect on 28-day mortality.